KAJIAN FAKTOR EKSPLOITASI BERDASARKAN JENIS POHON : STUDI KASUS DI SATU PERUSAHAAN HPH DI KALIMANTAN BARAT (A study on Exploitation Factor in Forest Harvesting Based on Trees Species : A case study in one forest concession holder in West Kalimantan) - Wesman Endom; Maman Mansyur Idris (Jurnal Penelitian Hasil Hutan, 1996)
Natural production forests  in Indonesia have been harvested since 1970.  In carrying out the harvesting of the forests, the goverment  used a parameter so called Exploitation Factor  (FE) as a basic calculation of annual allowable production.  Currently  the value of FE is 0. 7 regardless the species.  The value means that only about 70% of log volume can be extracted from  the  forest in the cutting operation.In this study an analysis of FE was carried out to see whether  it is necessary to differentiate the value based on tree species.  Data were collected  from  real logging activity in the forest. An analysis using Honest  by Significant  Difference  test showed that in reality there is no signifi cant difference among  the means of FE. This result justifies  the use of single value of FE for all species.Keywords:  Forest, harvesting, logs, conversion factor.